2014
DOI: 10.1088/2040-8978/16/5/055404
|View full text |Cite
|
Sign up to set email alerts
|

Dual-wavelength erbium-doped fiber laser with tunable wavelength spacing using a twin core fiber-based filter

Abstract: A dual-wavelength erbium-doped fiber laser with tunable wavelength spacing was proposed and experimentally demonstrated by using a twin core fiber (TCF)–based filter. Benefiting from the polarization dependence of the TCF-based filter, the laser operated in dual-wavelength oscillation with two orthogonal polarization states. By adjusting the polarization controller, the wavelength spacing was tuned from 0.1 nm to 1.2 nm without shifting the centre position of the two wavelengths. By stretching the TCF, the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Yin. et al reported a tunable DW-EDFL by adopting twin-core fiber (TCF) and achieved tunable bandwidth of 1.2 nm with the SMSR higher than 40 dB [16]. A four-wavelength switchable fiber laser based on twin-core EDF is achieved by Lian with a wavelength spacing of 1.1 nm and the SMSR higher than 43 dB [17].…”
Section: A Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Yin. et al reported a tunable DW-EDFL by adopting twin-core fiber (TCF) and achieved tunable bandwidth of 1.2 nm with the SMSR higher than 40 dB [16]. A four-wavelength switchable fiber laser based on twin-core EDF is achieved by Lian with a wavelength spacing of 1.1 nm and the SMSR higher than 43 dB [17].…”
Section: A Backgroundmentioning
confidence: 99%
“…A commercial splicer (Fujikura, FSM-100M) is used to splice one end of TCPCF with SMF using the core-to-core splice mode built in the machine. At the other end of TCPCF, we use the splice method depicted in [16] to monitor the output power in real-time. When it gets maximum, the lead-in and lead-out SMFs are aligned to the same core of TCPCF.…”
Section: A Fabrication Of the Tapered Tcpcf Filtermentioning
confidence: 99%
“…They demonstrated a tunable output laser line with 32 nm tuning range. Dual-wavelength EDFL with tunable wavelength spacing has been achieved using twin core [17], tapered EDF [18] and non-linear photonic crystal fiber (NLPCF) [10]. In [3,[19][20][21], stable multi-wavelength laser emission was obtained using in-line NLPCF MZI but with variable wavelength spacing.…”
Section: Laser Physicsmentioning
confidence: 99%
“…In this work, we proposed and experimentally demonstrated a tunable dual-wavelength and single-polarized fibre laser by use of a TCF-based filter [26]. Figure 8(b) illustrates the TCFbased filter with a TCF length, L 0 , of 1.1 m. In this section, we first presented the principle of the dual-wavelength fibre laser.…”
Section: Dual-wavelength and Single-polarized Fibre Lasermentioning
confidence: 99%